The chief data officer's playbook - Carruthers, Caroline (Facet, 2021)
This fully revised and updated edition of the bestselling Chief Data Officer's Playbook offers new insights into the role of the CDO and the data environment. Written by two of the world's leading experts in data driven transformation, it addresses the changes that have taken place in 'data', in the role of the 'CDO', and the expectations and ambitions of organisations. Most importantly, it will place the role of the CDO into the context of a c-suite player for organisations that wish to recover quickly and with long-term stability from the current global economic downturn.New coverage includes:the evolution of the CDO role, what those changes mean for organisations and individuals, and what the future might holda focus on ethics, the data revolution and all the areas that help readers take their first steps on the data journeynew conversations and experiences from an alumni of data leaders compiled over the past three yearsnew chapters and reflections on being a third generation CDO and on working across a broad spectrum of organisations who are all on different parts of their data journey.Written in a highly accessible and practical manner, The Chief Data Officer's Playbook, Second Edition brings the most up-to-date guidance to CDO's who wish to understand their position better; to those aspiring to become CDO's; to those who might be recruiting a CDO and to recruiters to understand an organisation seeking a CDO and the CDO landscape.